The integrated functions of the cardiac autonomic and vestibular/oculomotor systems in adolescents following severe traumatic brain injury and typically developing controls. (18th September 2020) - Sorek, Gilad; Gagnon, Isabelle; Schneider, Kathryn; Chevignard, Mathilde; Stern, Nurit; Fadida, Yahaloma; Kalderon, Liran; Shaklai, Sharon; Katz-Leurer, Michal
ABSTRACT: Introduction: The cardiac autonomic control system (CACS) is frequently impaired post-traumatic brain injury (TBI). However, the prevalence of vestibular/oculomotor impairment is less studied. These two systems interact during position change and contribute to blood-pressure regulation through the vestibulo-sympathetic reflex. Aim : To assess the CACS, the vestibular/oculomotor systems and their integrative function in adolescents post-TBI compared to typically-developing (TD) adolescents. Methods : 19 adolescents in the subacute stage following a severe TBI (14–117 days post injury) and 19 age and sex matched TD controls were recruited. Heart Rate Variability (HRV) was assessed at rest and during a modified tilt-test. A quantified version of the Vestibular/Ocular-Motor Screening (VOMS) was also administered. Results : At rest, the TBI group had higher HR and lower HRV values ( p < .001). All participants with TBI demonstrated impairments in the VOMS (median of positive tests: 5 [range 2–9]) compared to only 6 out of 19 in the TD participants (median 0 [0–2]) (z = −5.34; p < .001). In response to the modified tilt test, the HRV increased significantly in the lifting period and decreased significantly once in standing only in the TBI group (z = −2.85, p = .025). Conclusion : Adolescents post severe TBI demonstrated impairments in the CACS, positive tests on the VOMS and significantly greater changes in the modified tilt test as compared to TD. Clinical trial gov. number: NCT03215082